2015
DOI: 10.1111/phen.12104
|View full text |Cite|
|
Sign up to set email alerts
|

Probing the functional role of tick metalloproteases

Abstract: Abstract. Tick saliva assists feeding through a complex mixture of compounds that disarm the host homeostasis processes, such as platelet aggregation, vasoconstriction and blood clotting, as well as innate and acquired immune responses. Although the various properties of tick salivary glands have sparked great interest as candidate sources for anti-tick vaccines to prevent tick and tick-borne diseases, antigens that can be useful to induce an immune response against tick bites or the pathogens transmitted by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…Metalloproteases were also among the identified enzymes with 9% from the set of S class proteins in both of the genders. These enzymes require a metal ion, usually Zn 2+ , to catalyze the hydrolysis of a peptide bond [52]. These proteolytic enzymes have been found throughout almost the entire evolutionary scale from bacteria to mammals [53, 54].…”
Section: Resultsmentioning
confidence: 99%
“…Metalloproteases were also among the identified enzymes with 9% from the set of S class proteins in both of the genders. These enzymes require a metal ion, usually Zn 2+ , to catalyze the hydrolysis of a peptide bond [52]. These proteolytic enzymes have been found throughout almost the entire evolutionary scale from bacteria to mammals [53, 54].…”
Section: Resultsmentioning
confidence: 99%
“…While only 64 transcripts were overexpressed in H. dromedarii male SG, of which 41 had significant LFC, 81 transcripts were highly expressed in female ticks, of which 54 had a significant LFC. This protein family, which is commonly found in tick saliva, salivary glands, ovaries and the mid-gut, plays an important role in countering host inflammation, immunomodulation, fibrinolysis, blood protein digestion, nociception, vitellogenesis, remodeling the extracellular matrix and pathogen transmission [ 21 , 66 ]. Metalloproteases were characterized in several tick species: I. scapularis , A. americanum , Haemaphysalis longicornis , Rh.…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, it was evident from previous reports that outer membrane proteins are vaccine candidates and that cytoplasmic proteins are drug targets [ 21 , 109 ]. It is well known that exported proteins are the prominent molecules of interaction with cells infected by pathogens; therefore, they are potential candidates for vaccine targets [ 110 , 111 , 112 , 113 , 114 ]. The antigenicity and allergenicity analysis of target proteins revealed that eight among them were antigenic while the remaining four proteins were non-antigenic and all the target proteins were non-allergen ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%